Artificial intelligence in the academic elite: The use of AI in the world’s top 20 universities - Criado Davila, Yvette Vanessa; San Miguel Velásquez, Yuly Victoria; Idrogo Barboza, Gloria; Arce Vizcarra, Fernando Guillermo; Quispe Sánchez, Carmen Marisol (LACCEI, 2025)
Considering that universities are considered a locus of knowledge creation and professional training for future citizens, it is essential for them to be able to optimally use artificial intelligence in their academic lives. The research aims to evaluate the aspects found in the guidelines or protocols for the use of AI at the top 20 universities in the world. We conducted qualitative research using documentary analysis. The sample consisted of the top 20 universities in the world, according to the Times Higher Education World University Rankings 2025. The results revealed the need to digitally educate students in the use of artificial intelligence, ensuring data preservation and confidentiality, and addressing ethical issues. Also, the need was found to disseminate the use of AI in the educational community, and of IAGen tools, to know and disseminate the university’s AI use policies, along with topics in which AI can be used, such as: completion of course assignments, research activities, among others, as long as the teacher or the university allows its use and/or this is informed to the teacher.